2016
DOI: 10.3390/molecules21010078
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide and Hydrogen Sulfide in the Vasodilator Effect of Ursolic Acid and Uvaol from Black Cherry Prunus serotina Fruits

Abstract: Abstract:The present research aimed to isolate the non-polar secondary metabolites that produce the vasodilator effects induced by the dichloromethane extract of Prunus serotina (P. serotina) fruits and to determine whether the NO/cGMP and the H 2 S/K ATP channel pathways are involved in their mechanism of action. A bioactivity-directed fractionation of the dichloromethane extract of P. serotina fruits led to the isolation of ursolic acid and uvaol as the main non-polar vasodilator compounds. These compounds s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 69 publications
1
35
0
2
Order By: Relevance
“…Earlier studies have proved that naturally occurring lupane-, oleanane-, and ursane-type triterpenes elicit vasodilator effects [ 34 , 35 , 36 , 37 , 38 ]. The vasodilation produced by the lupane-type triterpene betulinic acid and the oleanane-type triterpenes moronic, morolic, and 3,4-seco-olean-18-enen-3,28-dioic acids is endothelium-dependent [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier studies have proved that naturally occurring lupane-, oleanane-, and ursane-type triterpenes elicit vasodilator effects [ 34 , 35 , 36 , 37 , 38 ]. The vasodilation produced by the lupane-type triterpene betulinic acid and the oleanane-type triterpenes moronic, morolic, and 3,4-seco-olean-18-enen-3,28-dioic acids is endothelium-dependent [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our research group previously demonstrated that ursolic acid and uvaol (the alcohol corresponding to ursolic acid) produce an endothelium dependent vasorelaxation, which involves stimulation of the NO/cGMP and H 2 S/K ATP pathways. Molecular docking studies showed that both triterpenes are able to bind with high affinity to endothelial NOS and CSE in allosteric binding sites located relatively far from the catalytic sites [ 34 ]. We found that corosolic acid ( 3 ) (EC 50 = 108.9 ± 3.2 µM; E max = 96.4 ± 4.2%) is approximately two fold less potent than ursolic acid (EC 50 = 47.1 ± 7.6 µM; E max = 97.7 ± 3.9%) and uvaol (EC 50 = 43.6 ± 5.6 µM; E max = 93.4 ± 5.1%) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La evaluación del valor nutracéutico y propiedades antihipertensivas de sus frutos permitió determinar que el extracto podría usarse en la prevención de la hipertensión y como coadyuvante en su tratamiento (Luna-Vázquez et al, 2013). Posteriormente se estableció que el ácido ursólico y el uvaol son los principales compuestos vasodilatadores no-polares en los frutos de capulín (Luna-Vázquez et al, 2016).…”
Section: Aprovechamiento Tradicional Y Moderno En Méxicounclassified